On phase transitions in the system of charged fermi particles above the liquid dielectric surface - Slyusarenko, Yu.V.; Lytvynenko, D.M.; Kirdin, A.I. (Вопросы атомной науки и техники, 2012)
A consistent theory of equilibrium states of charges and fields above the surface of liquid dielectric film located on a solid substrate is built. The developed approach is used for the description of phase transitions in these systems to the states with spatially-periodic ordering. Построена последовательная теория равновесных состояний зарядов и полей над поверхностью пленки жидкого диэлектрика, расположенной над твердой подложкой. Развитый подход использован для описания фазовых переходов в таких системах к состояниям с пространственно-периодическим упорядочением. Побудовано послідовну теорію рівноважних станів зарядів і полів над поверхнею плівки рідкого діелектрика, розташованої над твердою підкладкою. Розвинутий підхід застосовано для опису фазових перетворень у таких системах до станів із просторово-періодичним упорядкуванням.